Sugar transport across the plant vacuolar membrane: nature and regulation of carrier proteins. - Hedrich, Rainer; Sauer, Norbert; Neuhaus, H. ekkehard (Current opinion in plant biology, 2015)
The ability of higher plants to store sugars is of crucial importance for plant development, adaption to endogenous or environmental cues and for the economic value of crop species. Sugar storage and accumulation, and its homeostasis in plant cells are managed by the vacuole. Although transport of sugars across the vacuolar membrane has been monitored for about four decades, the molecular entities of the transporters involved have been identified in the last 10 years only. Thus, it is just recently that our pictures of the transporters that channel the sugar load across the tonoplast have gained real shape. Here we describe the molecular nature and regulation of an important group of tonoplast sugar transporter (TST) allowing accumulation of sugars against large concentration gradients. In addition, we report on proton-driven tonoplast sugar exporters and on facilitators, which are also involved in balancing cytosolic and vacuolar sugar levels.